PENGARUH PENERAPAN JAM KERJA TERHADAP RISIKO STRES KERJA PADA KARYAWAN PT. MOTIVE MULIA PLANT MASPION - Muhammad Zuhair Ujab; Dwi Faqihatus Syarifah Has (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
ABSTRAK Background: Work stress is condition that pushes oneself, one's soul beyond the limits of everyone's abilities, so that if it is not treated permanently it will have an impact on health. Indonesia's stress level rose 9% earlier to just 64%. Work stress is a major problem in Indonesia. People who are stressed at work can become chronically stressed and anxious. Research objectives: To analyze the effect applying working time to the risk of work stress at PT. Motive Mulia Plant Maspion. Method: Observational method with cross-sectional research method. total of 110 employees and 53 random samples. Questionnaires about working time and work stress were used research instruments, and simple logistic regression statistical tests were used analytical tests. Results: Most employees work during normal working hours, not less than 28 people or (52.8%) and most employees experience mild work stress, not less than 41 people or (77.4%). Statistical test results show that the value of P < significant; 0.037; to 0.05. Conclusion: Implementation of a work schedule has a significant effect on the risk of work stress for employees of PT. Motive Mulia Plant Maspion. employee who has worked more than the agreed number of hours must apply for overtime compensation. Keywords : Cement, Worker, Working Hours, Work Stres